Evaluación de riesgos laborales para el control de accidentes de trabajo en la empresa eduplastic, ubicado en Latacunga panamericana norte kilómetro 5 - Quinatoa Lema, Edgar Wilfrido (2016)
The research work is focused on industrial safety and occupational health at the “EDUPLASTIC COMPANY”, it does not have an occupational risk assessment to create a culture of risk prevention, and care of physical and mental integrity of all its employees about the risks exposed in different daily activities , that are making as well as administrative and operational staff. This being the main problem of this project, it is not breach with the safety standards, also it was showed several problems influence in this work, such as: descriptive and field, applying these gave to obtain information concerning the topic asked, for which the survey was conducted, and the risk matrix works with the technical standard prevention (NTP-330)….